PENGARUH MEDIA INTERNET SEBAGAI SUMBER INFORMASI BAGI PELAJAR DI SMK WONOMULYO KECAMATAN WONOMULYO KABUPATEN POLEWALI MANDAR - Sulhan Sulhan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2016)
This study aims to determine the effect of internet media (positive and negative impacts) on Wonomulyo Vocational School students and to describe the assessment of Wonomulyo Vocational School students in using internet media as a source of information. The data collection process prioritizes the emic perspective. This type of research is descriptive-quantitative to describe the picture of the influence of internet media as a source of information for students. Techniques for collecting data through surveys, questionnaires, interviews, and documentation to collect as much data as possible from the field relating to the influence of internet media as a source of information. The results of the study state that the main motivation of Wonomulyo Vocational School students using the internet is to find information that is closely related to school assignments. The internet makes it easy for every user to give and receive information from anyone, anytime and anywhere. The internet can facilitate the learning process at school. Internet media becomes the second teacher where everything related to subjects and other knowledge can find out by opening the internet media.